The Importance of Jargons in Different Fields of Language - Abduolimova, Maftunakhon; Osiyoxon, Nosirova (Journal of Innovation in Education and Social Research, 2024)
This article explores the impact of jargon in various fields, shedding light on the often obscure and exclusive language that can hinder communication. Through insightful analysis and examples, it emphasizes the importance of demystifying jargon to foster clearer understanding and inclusivity.